1991
DOI: 10.1017/cbo9780511895401
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Networks of the Hippocampus

Abstract: The questions of how a large population of neurons in the brain functions, how synchronized firing of neurons is achieved, and what factors regulate how many and which neurons fire under different conditions form the central theme of this book. Using a combined experimental-theoretical approach unique in neuroscience, the authors present important techniques for the physiological reconstruction of a large biological neuronal network. They begin by discussing experimental studies of the CA3 hippocampal region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
466
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 659 publications
(478 citation statements)
references
References 0 publications
11
466
0
1
Order By: Relevance
“…pathways of the hippocampus are the perforant path, the cingulum bundle, and the fimbria/fornix, which all arise from field CA1 and the subiculum (Traub and Miles, 1991;Magarinos et al, 1996). In this study, we found that synapsin I increased in DG/CA3 and decreased in CA1 region, suggesting that synaptic activity is excited within the hippocampal network and the output from the hippocampus is weakened in rats after 21 days of CUMS.…”
Section: Discussionmentioning
confidence: 49%
“…pathways of the hippocampus are the perforant path, the cingulum bundle, and the fimbria/fornix, which all arise from field CA1 and the subiculum (Traub and Miles, 1991;Magarinos et al, 1996). In this study, we found that synapsin I increased in DG/CA3 and decreased in CA1 region, suggesting that synaptic activity is excited within the hippocampal network and the output from the hippocampus is weakened in rats after 21 days of CUMS.…”
Section: Discussionmentioning
confidence: 49%
“…4.5 Ionic currents. Potassium (K + ) and Sodium (Na ++ ) currents I k and I Na in (1) are derived from Traub and Miles (2001), and are described as: (26) neurons (McCormick and Prince, 1985), and rat cortical layer 5 cells seem to be a preferential target for cholinergic innervation (Turrini et al, 2001). The known electrophysiological excitatory action is thought to be mediated by binding of ACh to muscarinic and/or nicotinic receptors on pyramidal neurons.…”
Section: Neurotransmitter Releasementioning
confidence: 99%
“…m, h, and n are the activation variables whose time evolution depends on the (voltage-dependent) rate constants a m , b m , a h , b h , a n and b n . The voltagedependent expressions for the rate constants were modified from the model described by Traub and Miles (1991):…”
Section: Hodgkin-huxley Modelsmentioning
confidence: 99%